Pelaksanaan Fungsi Pengawasan Badan Permusyawatan Desa (Studi di Desa Ayong Kecamatan Sangtombolang Kabupaten Bolaang Mongondow) - Djaafar, Lucyane; Hamid, Saleh Al (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The BPD institution as a village institution is an important component in carrying out village development in order to realize village prosperity and independence. The aim of this research is to analyze the implementation of the BPD's supervisory function in Ayong Village, Sangtombolang District, Bolaang Mongondow Regency. This research method is qualitative research, namely to analyze the Implementation of the Supervisory Function of the Village Consultative Body. The results of this research are that the implementation of the supervisory function of the Village Consultative Body in Ayong village has not met the community's expectations, where it is still found that several parts of the community's aspirations have not been fulfilled. The community is not satisfied with the services of the Village Consultative Body, because the aspirations they have conveyed have not been responded to well.